ANALISIS PENGARUH DESENTRALISASI DAN SISTEM AKUNTANSI MANAJEMEN TERHADAP KINERJA MANAJERIAL (STUDI KASUS PADA PT. CHAROEN POKHPAND INDONESIA TBK. CABANG MAKASSAR) - Hasan, Asriani; Randi, Randi (Jurnal Riset Akuntansi Politala, 2020)
This research aims to determine the influence of decentralization and accounting management system against managerial performance at PT. Charoen Pokhpand Indonesia Tbk Makassar Branch. This research implements quantitative methods using multiple linear regression analyses. The data in this research is data obtained from respondents PT. Charoen Pokhpand Indonesia Tbk. Makassar Branch by sampling 60 respondents. The granting of the questionnaire was used as a method for collecting data. In this study obtained a constant value of 27.604. Value of significance for decentralized influence  to managerial performance  of  with value    and coefficient value of 0.264. Next, Value of significance for decentralized influence  to managerial performance  of with value    and  regression coefficient value of . Findings from this study suggest that managerial performance is influenced by decentralization and accounting management systems. It can be concluded that decentralization and management accounting systems are both used in decision making to improve performance on the company.